STRATEGI KOMUNIKASI KONSULTAN MANAJEMEN WILAYAH DALAM PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KELURAHAN TANAH DATAR KECAMATAN PEKANBARU KOTA - Sylvia Yolanda; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Currently there are slums in urban Indonesia, it means the people still live in conditions of homes uninhabitable and lack of public access to urban basic services. Kota Tanpa Kumuh Program (Kotaku) launched in 2016 which is a program of prevention and improving the quality of national slum. Tanah Datar is a priority locations considered successful running KOTAKU program, this is not apart of their communication strategy. This study aims to determine the communicator, target audience, media and message strategy communications made in the course of Regional Management Consultants on Kota Tanpa Kumuh Program of Tanah Datar District of Pekanbaru City.This research method is qualitative descriptive method using strategic communications theory. The research subject is determined by purposive sampling with 9 informants. Data collection techniques include observation, interviews, and documentation. Data was analyzed using interactive model of Miles and Huberman, the validity data checking techniques includes extension of participation, and triangulation.The results showed first, form a strategy that assigns a team of facilitators and skilled team of Regional Management Consultants, and chairman of the Institute for Community Self-Reliance Tanah Datar Makmur as a speaker in the socialization. Second, audience strategy is the entire village community Tanah Datar. Third, message strategy is the preparation of the material comprising the message dissemination of relevant information Kota Tanpa Kumuh Program, as well as the use of the slogan and adjustments in the delivery of the message to the target. Fourth, the using of media that is the media group with the dissemination and use of mass media such as print media (newspapers, brochures, banners and billboards, pamphlets and fotonovela bulletin) and electronic media (online media, radio, social media facebook and instagram, and website).Keywords: Communication Strategy, Slum, Strategic Communication